Study on seed anatomy of Sungkai (Peronema canescens Jack); a viability perspective - USEP SOETISNA (Biodiversitas Journal of Biological Diversity, 2005)
Sungkai (Peronema canescens Jack) is a member of Verbenaceae family. It has been registered on the National Industrial Timber Estate Programme. Its large-scale propagation was usuallly carried out by vegetative or stem cuttings, therefore it had significant limitation. Due to the low germination rate, so the generative propagation was not yet a prime target. Fruits as well as flower biology remain open so intensive study. Beside the case of low germination rate, the purity test on the whole fruits resulted in an assumption on three categories, i.e. (i) low percentage of fruits containing full seeded segment, (ii) fruits posses a splitting mechanism into separate half-seeded fruit, (iii) morphologically difficult to recognize a full-seeded fruit.Â Key words: Peronema canescens, seed, viability.